Internet connectivity disruption in Benin (Benin) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Benin. Data sourced from IODA.
Network Disruption Incident ID: BJ-2026-0017. Severity: critical. Confidence: 65%